Evaluation of seismic passive earth pressure of inclined rigid retaining wall considering soil arching effect. Issue 100 (September 2017) - Pain, Anindya; Chen, Qingsheng; Nimbalkar, Sanjay; Zhou, Yitao
Abstract: Evaluation of seismic passive earth pressure is an important topic of research in geotechnical engineering. In this study seismic passive pressure on an inclined rigid retaining wall supporting horizontal cohesionless backfill is estimated considering arching effect. A planar failure surface is considered in the present analysis. Seismic forces are considered to be pseudo-static in nature. The effect of different parameters on the seismic passive earth pressure is studied in details. The normal stress distribution along the depth of the backfill is found to be nonlinear in nature. Friction angle between wall and the backfill soil has the most significant effect on the distribution of normal stress along the depth of the backfill. The point of application of seismic passive pressure shifts gradually downward for higher seismic forces. Present method is validated with the experimental results available in the literature for static conditions. Comparison of present method with other theories is also presented showing the merit of the present study. Arching effect in the backfill should be considered for high values of wall inclination angle as the present seismic passive resistance is found to be the lowest as compared to other theoretical solutions. Highlights: Solution of seismic passive earth pressure of inclined rigid retaining wall is proposed. Combined effects of arching in cohesionless soil and wall friction are considered. Solution considers uniformly distributed surcharge load at the top of the backfill. The proposed method is validated using the available theoretical solutions.